Prototipe Sederhana Sistem Deteksi Kriminal Berbasis Internet Of Things Menggunakan Teknologi YOLOv5 - Nurfal Aziz, Afris; Khoiriyah, Hani’atul; Abdillah, Fauzan; Wiryawan, I Gede (Komputika : Jurnal Sistem Komputer, 2024)
Crime is any action or thing carried out by an individual, group or community that violates the law or is a criminal act, which disturbs social balance or stability in society. One of the tools used to monitor security in various places such as homes, offices and other public places is Closed-Circuit Television (CCTV). However, even though many CCTVs have been installed, many crimes still occur due to limitations in monitoring and supervision by security officers. Therefore, developing a crime detection system on CCTV using deep learning methods is considered important to increase security and reduce crime rates. The aim of a criminal detection system is to increase security and prevent criminal acts in a certain area or place. The technology used is YOLOv5 and is supported by Internet of Things-based hardware. The system succeeded in detecting violence objects 92% of the time and robbery 91% of the time in initial testing without background. In the second background test, the system succeeded in detecting violence objects 93% of the time and robbery 53% of the time. The system succeeded in detecting violence objects 91% of the time and robbery 83% of the time in real-time testing.